Code Switching Analysis on You-Tube Channel #NebengBoy by Boy William - Wibiani, Putu Findi Desi; Budiasa, I Gede; Shanti Sari Dewi, Anak Agung Sagung (Humanis; Vol 25 No 3 (2021), 2021)
This study is entitled "Code-Switching Analysis on YouTube Channel "#NebengBoy by Boy William”. The aim of the study is to analyze the type and the function of code-switching on the Boy William YouTube Channel. The data is collected from the YouTube Channel of Boy William which is taken from Maudy Ayunda and Sandra Dewi episodes. The method and technique of collecting data is the documentation method, and the analysis is done by the qualitative method. The theory that is used to analyze the types and functions of code-switching is Apple & Muysken's theory (2015). Three types of code-switching are found namely tag switching, intra-sentential switching, and inter-sentential switching, and their six functions, namely referential function, directive function, expressive function, phatic function, metalinguistic function, and poetic function. Nonetheless, the metalinguistic function is not found in the analyzed data.